PENENTUAN TINGKAT CASH HOLDING OPTIMAL PADA PERUSAHAAN SEKTOR NONFINANSIAL DI BURSA EFEK INDONESIA - Herawan, Yuki
The purpose of this study is to investigate the optimal level of cash holding that produces optimal returns. The threshold panel regression model is applied to test the threshold effect of the cash holding ratio on firm’s profitability of 311 non-financial companies listed on the Indonesia stock exchange market (BEI) during the period of 2015-2019. In addition, the fixed-effect panel data regression model is also applied to determine the effect of leverage, liquidity, profitability, dividend payment, and company size on cash holding to provide policy implications for non-financial companies listed on the Indonesia stock exchange market in determining the proportion of cash holding. The results showed that a single-threshold effect exists between the cash holding ratio and the company's profitability. The coefficient is positive when the cash holding ratio passes the 6.53% level and the coefficient below the threshold is negative. Therefore, it is concluded that the relationship between profitability and cash holding is nonlinear in accordance with the trade-off theory. The results of the fixed-effect panel regression model can be used in determining company policies to optimize the company's cash holding level. The liquidity variable is proven to be in accordance with the theory, which is useful as a cash substitute asset if needed. With large liquidity, the company is more freely to store cash in smaller amounts. In the leverage variable, it is obtained in accordance with the theory that the higher the leverage ratio will motivate the company to save more cash in order to avoid bankruptcy. High cash flow volatility in the company will also encourage companies to hold more cash. Company size in Indonesia is correlated with greater and stable profitability, so large companies are likely to have less cash reserves. While the payment of dividends should be an option for companies to collect cash, but in Indonesia itself it was found that companies rarely pay dividends so that in this study it is not significant to the level of cash. If the cash holding level is below the optimal level, it is recommended to increase the liquidity ratio as a cash substitute and to enhance the company's profitability. Meanwhile, if the cash holding level is above the optimal threshold level, it is recommended to reduce the leverage ratio to ensure the company’s cash holding and profitability.